2011
DOI: 10.1007/978-1-4614-1566-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Colored Light and Brain and Muscle Oxygenation

Abstract: Colored light is applied in medicine in the treatment of various diseases. The aim of this study was to investigate potential effects of exposure to blue and red light on brain and muscle blood volume ([tHb]) and tissue oxygenation (StO2) measured by noninvasive near-infrared spectrophotometry (NIRS). Ten healthy volunteers were included in a randomized crossover study. Blue light exposure leads to decreased oxygen consumption in the brain and the skeletal muscle. I ntr oductionLight of different colors (CL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
1
11
1
Order By: Relevance
“…Surprisingly, also, no significant difference between the blue and red light was observed. The latter may seem in contrast to the previous study [24], where highly significant differences between red and blue were detected. In this study, the changes are similar to those observed for red light in the previous study.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Surprisingly, also, no significant difference between the blue and red light was observed. The latter may seem in contrast to the previous study [24], where highly significant differences between red and blue were detected. In this study, the changes are similar to those observed for red light in the previous study.…”
Section: Resultscontrasting
confidence: 99%
“…Again, for an easier understanding, we first summarize the findings of the previous publication [24]. In the leg, the THI significantly increased by 1.1 (blue) or 1.5 µM (red) continuously in the course of time and independently of the color, which was interpreted as reduced venous drainage, an accumulation of blood, and consequent venous pooling in the calf muscle during the measurement due to the sedentary position of the subjects.…”
Section: Changes In the Calf Musclementioning
confidence: 87%
See 3 more Smart Citations